Flowering Plants. Monocots 2015
DOI: 10.1007/978-3-319-15332-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Systems

Abstract: Reproductive systems in the grasses are diverse. This section begins by describing the morphological variation in placement of the stamens and pistils, and then follows with discussion of outcrossing, self-pollination and apomixis. UNISEXUAL VS. BISEXUAL FLOWERSGrasses may have unisexual or bisexual flowers. Because of the distribution of the unisexual versus bisexual condition in the immediate outgroups and early diverging taxa, attempts to determine the ancestral condition for the family are highly sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Despite frequent events of genomic repatterning and gene losses, which have caused considerable divergence in genome size in the grass family (Bennetzen and Wang, 2018), genes have tended to maintain their position in chromosomes with strict conservation of gene order (collinearity) or gene co-localization (synteny) (Wang et al, 2015 and references therein). Since grass genomes are largely syntenic and apomixis occurs throughout the grass family, several authors have thought that the same set of genes may control apomixis in grasses (Kellogg, 2015). However, while the regions controlling apomixis are similar within genera (Pupilli et al, 2004;Akiyama et al, 2011), they can be highly divergent between genera (Ozias-Akins, 2006).…”
Section: Evolution Of the Apomixis Locus Within The Gramineaementioning
confidence: 99%
“…Despite frequent events of genomic repatterning and gene losses, which have caused considerable divergence in genome size in the grass family (Bennetzen and Wang, 2018), genes have tended to maintain their position in chromosomes with strict conservation of gene order (collinearity) or gene co-localization (synteny) (Wang et al, 2015 and references therein). Since grass genomes are largely syntenic and apomixis occurs throughout the grass family, several authors have thought that the same set of genes may control apomixis in grasses (Kellogg, 2015). However, while the regions controlling apomixis are similar within genera (Pupilli et al, 2004;Akiyama et al, 2011), they can be highly divergent between genera (Ozias-Akins, 2006).…”
Section: Evolution Of the Apomixis Locus Within The Gramineaementioning
confidence: 99%
“…switch from floral development to vegetative development) that leads to the formation of leafy shoots or bulbils . Transitions between pseudovivipary and sexual reproduction have been observed in both directions in experimental set ups and in natural populations . While flower reversion has been traditionally explained by genetic causes, Wang et al showed that in rice pseudovivipary is, at least partly, regulated by an epigenetic mutation.…”
Section: Does Esd Have An Epigenetic Basis?mentioning
confidence: 99%